2019
DOI: 10.1007/s10915-019-01028-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Moving Least Squares and RBF+poly for Interpolation and Derivative Approximation

Abstract: The combination of polyharmonic splines (PHS) with high degree polynomials (PHS+poly) has recently opened new opportunities for radial basis function generated finite difference (RBF-FD) approximations. The PHS+poly formulation, which relies on a polynomial least squares fitting to enforce the local polynomial reproduction property, resembles somehow the so-called moving least squares (MLS) method. Although these two meshfree approaches are increasingly used nowadays, no direct comparison has been done yet. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Santos et al [48] compared the performance of stabilized flat Gaussian RBFs with PHS-RBF for two dimensional Poisson equation and observed that the PHS approach is more robust and computationally more efficient than the stabilized Gaussian RBFs. Bayona [49] compared a local weighted least squares approach with polynomial basis and the PHS-RBF method for interpolation and derivative approximation. The choice of weighting function is a difficulty in the least squares approach and was found to fail at high polynomial degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al [48] compared the performance of stabilized flat Gaussian RBFs with PHS-RBF for two dimensional Poisson equation and observed that the PHS approach is more robust and computationally more efficient than the stabilized Gaussian RBFs. Bayona [49] compared a local weighted least squares approach with polynomial basis and the PHS-RBF method for interpolation and derivative approximation. The choice of weighting function is a difficulty in the least squares approach and was found to fail at high polynomial degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works [9][10][11][12] have looked to find point locations for finite-difference methods but do not formulate piecewise-defined Lebesgue constants and have not focused on RBF-FD methods using PHSs and polynomials. A few works, however, have considered Lebesgue constants for RBF-FD methods for other purposes [21,22].…”
Section: Node Sampling For Rbf-fd Methodsmentioning
confidence: 99%
“…Flatter functions give higher accuracy but result in coefficient matrices of high condition numbers [39][40][41][42][43][44][45][46][47][48][49]. Appending polynomials to the RBF has been shown to give high accuracy, depending on the degree of the highest monomial appended [19][20][21][22][50][51][52][53][54][55][56]. Ideally, high order of accuracy can be achieved by appending suitably high order monomials.…”
Section: Multiquadrics (Mq)mentioning
confidence: 99%